Policy Consider of Green Chemistry in Indonesia - Maresi, Sinta Ramadhania Putri (Politeknik AKA Bogor, 2025)
Green chemistry frameworks in Indonesia encompass a range of regulatory, industry-specific, and policy initiatives aimed at promoting sustainable industrial practices and aligning with global sustainability goals. In Indonesia, where industrial activities and environmental concerns are significant, the application of green chemistry can play a crucial role in fostering a more sustainable future. This research explores the potential impact of green chemistry on Indonesian industry, focusing on its integration within the framework of the Omnibus Law on Job Creation (No. 11/2020) and its alignment with the Sustainable Development Goals (SDGs). Green chemistry, which emphasizes the design of products and processes that minimize the use and generation of hazardous substances, offers a strategic approach to achieving sustainable industrial development in Indonesia. A comprehensive literature review will be conducted to understand the current state of green chemistry practices in Indonesia. This review will draw upon a wide range of sources, including academic journals, government reports, policy papers, industry publications, and relevant case studies. The combination of supportive regulatory frameworks, industry adoption, and alignment with global sustainability goals positions alignment with global sustainability goals positions Indonesia to advance towards a greener, more sustainable future.